Complicated vivax malaria in pregnancy: A case report in rural area of Indonesia - Surya, Raymond; Manurung, Edward Sugito; Saroyo, Yudianto Budi (Universitas Airlangga, 2023)
HIGHLIGHTS In malaria endemic area, pregnant women are highly prone to suffer from malaria infection. Vivax malaria in pregnancy can contribute to anemia and preterm delivery. ABSTRACT Objective: This study aimed to report a preterm delivery and anemia as part of P. vivax malaria infection complications in a pregnant woman in Timor Tengah Selatan regency, East Nusa Tenggara, Indonesia. Case report: A 42-year-old pregnant woman, gravida 6 para 5,36-week of gestational age pregnant woman came with complaints of water breaking since one day before admission. She had fever with chills for three days, especially at night along with muscle, headache, joint soreness, dizziness, and palpitations. Rapid diagnostic test for malaria showed positive result. Peripheral blood smear examination revealed microcytic hypochromic due to iron deficiency or chronic infection and presence of trophozoites-ring form of P. vivax with 4,235 parasitemia. A baby boy was born with weight of 2,470 grams (percentile 28%), fetal head 31 cm (percentile 13%), birth length 43 cm (percentile 4%), and Apgar Score (AS) 8 and 9 at 1 and 5 minutes, respectively. The treatment was provided according to anti-malarial guideline in Indonesia using dihydroartemisin 120 mg and piperaquine phosphate 960 mg fixed dose as DHP for 3 days and primaquine 15 mg for 14 days. Conclusion: Anemia as part of vivax malaria complication in pregnancy contributes to preterm delivery.